Logística reversa: um estudo sobre a aplicação do alumínio na produção de panelas na fábrica MDM, na cidade de Manaus - Silva, Ayla Nascimento da. (Brasil, 2025)
The study investigates the implementation of reverse logistics in the production of aluminum cookware at the MDM factory in Manaus, with the aim of recapturing value and ensuring the proper disposal of waste. The aim is to understand how reverse logistics is applied in the manufacture of cookware and kitchen utensils, using recycled aluminum discs as raw material. The methodology included visits to the factory, documentary research and the application of Likert Scale forms to employees and the owner. The results showed a high level of appreciation for reverse logistics practices by employees and recognition of the environmental and economic benefits, with a SWOT analysis highlighting strengths such as commitment to sustainability and efficiency in aluminum recycling, as well as identifying operational challenges, partnership opportunities and regulatory threats. The conclusion is that reverse logistics at MDM promotes environmental sustainability and generates economic benefits, in line with the demands for sustainable business practices. The laws and regulations analyzed reinforce the importance of public policies to promote these practices and foster a more circular and resilient economy.